Perception on the factors influencing potential candidates to select their employers - V.J., DR. MAHESH; K.J., SAI KUMAR (The journal of contemporary issues in business and government, 2020)
Career is an imperative aspect of everyone's life and it has a huge impact on the lifestyle, quality of life, and thereby happiness. Hence, a lot of variables are involved while selecting an organisation. Variables can often differ according to an employee’s personal obligations, life requirements and career path. The objective of this research is to compare the major factors that can influence a potential candidate while selecting an employer. The factors considered for this research are financial benefits, commuter benefits, paid leave benefits and healthcare packages. This study involves quantitative analysis where a questionnaire was distributed to 106 UG/PG graduates. The hypotheses were tested using the Anova analysis method. The results of the research revealed that the health care package is the important factor that can influence the candidate to select an employer. This research can be useful for an organisation to improve their recruitment policy and employee wellness.